Intercalation processes and diffusion paths of lithium ions in spinel-type structured Li1+x Ti2 O4: Density functional theory study - Anicete-Santos, M.; Gracia, L.; Beltrán, A.; Andrés, J.; Varela, J. A. [UNESP]; Longo, E. [UNESP] (American Physical Society (APS), 2008)
Intercalation processes and corresponding diffusion paths of Li ions into spinel-type structured Li1+x Ti2 O4 (0≤x≤0.375) are systematically studied by means of periodic density functional theory calculations for different compositions and arrangements. An analysis of the site preference for intercalation processes is carried out, while energy barriers for the diffusion paths have been computed in detail. Our results indicate that the Li insertion is thermodynamically favorable at octahedral sites 16c in the studied composition range, and Li migration from tetrahedral sites 8a to octahedral sites 16c stabilizes the structure and becomes favorable for compositions x≥0.25. Diffusion paths from less stable arrangements involving Li migrations between tetrahedral and octahedral sites exhibit the lowest energy barrier since the corresponding trajectories and energy profiles take place across a triangle made by three neighboring oxygen anions without structural modification. Theoretical and experimental diffusion coefficients are in reasonable agreement. © 2008 The American Physical Society.